Dietary Habits of Iraqi Women with Breast Cancer at Oncology Hospitals in Baghdad City: Comparative Study - Hadeel Mousa Mahalhal1 , Hawraa Hussein Ghafel2 (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Dietary pattern explains the overall diet; the food, food groups and nutrients included; theirvariety and combination. Breast cancer is the most prevalent cancer among women worldwide. Many riskfactors for breast cancer contribute to personal habits, such as diet and exercise. Certain risk factors linkedto lifestyle include decisions to have children and to take medicines containing hormones.Objectives of the study : To assess women’s dietary Habits, Foods Choices, and to find out the relationbetween demographic characteristics and breast cancer.Methodology: Adescriptive and analytic study, non-probability (a purposive sample) consist of (100)women was carried out at three Oncology Hospitals in Baghdad City, Iraq.The study group consist of(100)women divided in two groups the first one include (50) women as a (study group) that attending An oncologyHospitals and the second include (50) women as a (control group) that attending the Primary Health CareCenters.Results: women in both groups are consuming red meat with low frequency and amount than normalconsumption . More than half of women with breast cancer are eating red meat one time per week (54%)while those without breast cancer are eating red meat two times per week (50%).Conclusion: women in both groups are consuming red meat with low frequency and amount than normalconsumptionRecommendation Avoid eating canned and processed red meat with preservatives and replaced it withfresh well cooked meat. Community orientation towards a healthy, balanced nutrition that contains the basicelements that the body needs without focusing on a specific food. Activation the role of media in increasethe awareness of women in the community about healthy diet. Instruct women with breast cancer to followa healthy diet guideline and avoid eating canned and processed red meat with preservatives during theirtreatment courses.